Vegetative propagation of bactris gasipaes (peach palm) by clump division for production of palm seeds - Yuyama, Kaoru; Flores, Wanders B.Chávez (Acta Horticulturae, 2013)
A breeding program consisting of selected plant multiplication was undertaken so as to find a more appropriate technology for the division of peach palm clumps. Its experimental design were randomized block with three replicates,in a 3×5 factorial scheme, where the factors were offshoot height (<30, 30-60, >60 cm) and time length following separation (0, 30, 60, 90 and 120 days). Findings indicate that the 30 to 60 cm high offshoot ought to be left out in the field for at least one month so it may heal after having been separated from the clump so that it will attain above 65% seedling survival rate, while those left for four months presented 80% of survival rate. There was an asexual propagation technique with high survival rate of offshoot separated from the mother plant or clump in any palm species. This technique was to just review the technique used by other authors and introducing the part where failures can have committed the conduct. Like all living things when the offshoot are separated from the clump, leaving a scar open, and the tillers need to recover not only the roots to feed and heal the scars caused by forced separation, using existing reserves. This new technique only introduced or minimized the problem of the offshoot in 50%. The offshoot are separated from the clump, but will remain in the same place until wound healing, feeding on the same root.